Impact of socio-economic status and other associated factors on women’s access to mammography in Eastern Morocco - Bakloul, Nacer; Bougarne, Loubna; Bouchefra, Said; Elaissaoui, Fouzia; Elharchli, El Hassan (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Breast cancer is an international public health problem. This study explored the association between the performance of mammography and the socio-economic status (SES) of participants and other associated factors. Methods: This prospective cohort study was spread over one year (November 2023 - October 2024), and included 103 women from the province of Taza, aged between 23 and 64 years and of different SES. Data were collected from the patient’s files and completed by a questionnaire with the participants. Statistical analyses, including univariate and multivariate methods, were conducted to assess the association between the investigated factors and the accessibility of mammography. Results: The study population consisted mainly of women aged 40-59 years (73.8%), married (75.7%), living in rural areas (62.3%), and representing various SES. Only 48.5% of the participants had mammograms, unevenly distributed according to SES. Women of low SES were two and a half fold more likely not to have their mammograms, due to financial constraints, lack of awareness, and inaccessibility of services. Lack of awareness (ARR = 4.321 95% CI: 1.753-10.653) and late appointments (ARR = 12.5 95% CI: 2.711-57.644) were also among the main obstacles. Conversely, factors such as fear of a positive diagnosis (ARR = 0.071 95% CI: 0.026-0.192) and financial support (ARR = 0.005 95% CI: 0.001-0.044) proved protective. Conclusion: The study highlighted the importance of targeted interventions, such as financial support and awareness-raising, in removing barriers to screening and improving access to mammography for vulnerable populations.